THE INFLUENCE OF ACCESS TO CAPITAL AND CREATIVITY ON THE PERFORMANCE OF MSMEs IN THE READY-TO-EAT CULINARY SECTOR IN WEST PADANG DISTRICT - Lini Febrianti; Mike Kusuma Dewi; Dewi Zulvia; Laynita Sari (UPT Publikasi Ilmiah UNISBA, 2026)
This study aims to examine the influence of access to capital and creativity on the performance of Micro, Small, and Medium Enterprises (MSMEs) in the ready-to-eat culinary sector in West Padang District, Indonesia. A quantitative research approach was employed using multiple linear regression analysis. The population consisted of 1,922 ready-to-eat culinary MSMEs, and a sample of 95 respondents was selected using the Yamane formula with a 10% margin of error. Primary data were collected through a structured questionnaire using a five-point Likert scale. The results indicate that access to capital does not have a significant effect on MSME performance, whereas creativity has a positive and significant effect. These findings suggest that creativity plays a more important role than access to capital in improving MSME performance through product innovation, packaging development, and marketing strategies.